Patterns of Social Adjustment in Hearing-Impaired Children at the Early Childhood Stage - Kushawaha, Abhiram; Alvera, Bushra (CV. Rayyan Dwi Bharata, 2026)
Early childhood is a critical period for the development of social and emotional competencies that underpin later academic success and psychological well-being. Children with hearing impairment often encounter significant communication barriers that may hinder peer interaction, emotional regulation, and overall social adjustment. The present study examined the patterns of social adjustment among hearing-impaired children aged 4–6 years and compared outcomes across inclusive and special early childhood settings. A descriptive survey design was employed with a sample of 60 children. Data were analysed using mean, standard deviation, t-test, and Pearson’s correlation. Findings revealed that children enrolled in inclusive preschools demonstrated significantly higher social adjustment scores than those in special schools (t = 4.21, p .05). A strong positive correlation (r = 0.62) was observed between communication competence and social adjustment, indicating that improved expressive and receptive skills enhance peer participation and social confidence. No significant gender differences were found. The study highlights the importance of early intervention, communication development, and inclusive pedagogical practices in promoting positive psychosocial outcomes among hearing-impaired children.